Effects of hypercapnic-hypoxic training on respiratory muscle strength and front crawl stroke performance among elite swimmers - Dajana Karaula; Goran Leko; Jan Homolak (Türk Spor ve Egzersiz Dergisi)
The aim of this resent study was to determine the effects of an 8-week hypercapnic-hypoxic (H-H or apnea) training program on respiratory muscles strength and 100 meter crawl swimming performance. The study was conducted on a sample of 26 Croatian elite swimmers (experimental group [EG] n=12, control group [CG]   n=14). Both groups were subjected to the same swimming training programs and training sessions on a treadmill. The experimental group was additionally subjected to hypercapnic-hypoxic training program with increased muscular activity. Date on the following outcome variables were collected: the strength of respiratory muscles (maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP)), 100m front crawl swimming time (R100m) and breathing frequency during the same test (BF100m). A series of two way repeated measures ANOVAs has shown significant interactions between group (EG and CG) and the repeated-measure factor (pre- and post-test) (MIP: p = 0.006, MEP: p lt; 0.001, R100m, p lt; 0.001, FB100m, p lt; 0.001), all showing greater efficacy of the experimental program. It seems that the hypercapnic-hypoxic training program may provide substantial benefits for elite swimmers, in addition to their standard training sessions.